Poverty and Foreign Aid Evidence from Recent Cross-Country Data - Abuzar Asra; Gemma Estrada; Yangseon Kim; M. G. Quibria (Asian Development Bank (ADB), 2005)
This paper takes a fresh look, from a macro perspective, at the issue of aid effectiveness. An important point of departure for this study is that it adopts poverty reduction, as contrasted from economic growth, as the metric for measuring aid effectiveness. In conducting the empirical investigation, the paper experiments with a number of different regression equations and uses a new panel dataset on poverty. It shows that aid and aid-squared both have significant coefficients but with different signs (positive for aid and negative for aid-squared). This result suggests that aid is effective when it is relatively moderate but becomes ineffective when the size of aid exceeds the critical value defined by the absorptive capacity. Our results further suggest that while the macro policy environment and the quality of governance have a significant bearing on poverty reduction, aid effectiveness is not critically contingent on them. Aid has on average been effective, our regression results confirm, under a whole variety of circumstances - in terms of policy environments and quality of governance - in a wide diversity of developing countries. It also points to the limited usefulness of using aggregative index of (macroeconomic) policy and governance for policy insights. To derive useful policy insights, one needs to look beyond these aggregates. Hopefully, the present paper, which makes an exploratory first attempt in directly linking poverty reduction (rather than growth) to aid, controlling for a number of macroeconomic policy variables and governance, would inspire further future research efforts
hdl:11540/1895
Keywords: 330; Armut; Entwicklungshilfe; Entwicklungspolitik; Entwicklung